PENGARUH KECERDASAN EMOSIONAL, MOTIVASI KERJA DAN KOMITMEN KERJA TERHADAP KINERJA KARYAWAN DI YAYASAN AL-HUDA PEKANBARU - Mustika, Aai (Eko dan Bisnis: Riau Economic and Business Review, 2018)
This study entitled Influence of Emotional Intelligence, Work Motivation and Work Commitment to Employee Performance at Al-Huda Foundation Pekanbaru. This study aims: To determine the Influence of Emotional Intelligence, Work Motivation and Working Commitment together to Performance Employees. And to know the Influence of Emotional Intelligence, Work Motivation and Work commitment partially on Employee Performance. This research is carried out in Yayasan Al-Huda Pekanbaru by using samples of 45 employees. Analysis of data by using multiple regression with the help of SPSS program Persi 20. Based on the data and analysis that has been done, it can be taken some conclusions as follows: Variables of Emotional Intelligence, Work Motivation and Work Commitment together to positively and significantly influence on Lecturer performance, 96.1% while the remaining 4.9% influenced other variables that are not discussed in research such as competence, organizational culture and compensation. Contribution The influence of the above three independent variables on Employee Performance of 96, 1% The rest is influenced by other variables that are not examined. Emotional Intelligence variable partially does not have a positive and significant effect on employee performance. While the variable of Work Motivation and Work Commitment partially have positive and significant influence to Employee Performance. Thus Work Motivation Can Be Maintained and Work Commitment can be improved, if improved will be able to improve Employee Performance in Al-Huda Foundation Pekanbaru